From bench to bedside: the realities of reducing global prostate cancer disparity in black men - Roberts, Robin (Cancer Intelligence, 2014)
Prostate cancer in black men of African descent has a different tumour biology compared to those of other races. Its clinical manifestations depict a more aggressive disease with higher morbidity and mortality. This study proposes, through a literature search, identifying applied laboratory and clinical research in prostate cancer directed to improve outcomes and decrease global disparities of prostate cancer in black men of African descent. This review identified five categories pertinent for research: prostate-specific antigen (PSA) testing for early detection and screening, the potential of epigenetics, cultural determinants and health-seeking behaviours, other biomarkers for prostate cancers, and the economics of treating advanced prostate cancer. The analysis revealed that in developed countries, men of African descent are underrepresented in the sampling pools in both laboratory and clinical research, and thus the applicability and relevance of these results to men of African descent are circumspect. However, developing countries with high populations of black males have limited laboratory and clinical research publications. This is due to limited funding to support research programmes and basic clinical services for early detection and treatment. The study concludes that for the involvement of developing countries in bench research, they should do it in collaboration, like fostering partnerships with credible academic-based institutions and organisations. This requires a realm of transparency, respect, protection of the rights and dignity of the patients, and an equity in participation and sharing of the benefits to be accrued. The current transatlantic and Caribbean collaborations in research, education, and health service delivery in prostate cancer care for men of African descent exemplify the successes of such partnerships.